2022
DOI: 10.5398/tasj.2022.45.3.319
|View full text |Cite
|
Sign up to set email alerts
|

Egg Production, Egg Quality, and Fatty Acid Profile of Indonesian Local Ducks Fed with Turmeric, Curcuma, and Probiotic Supplementation

Abstract: Indonesian local ducks are commonly raised for egg production purposes. However, the performances of these ducks are still variable and must be improved. This study investigated the effects of turmeric, curcuma, and probiotic supplementations on the egg production and quality of Indonesian local ducks, emphasizing the eggs' fatty acid profile. Two hundred female local ducks aged 16 weeks were randomly allotted to four dietary treatments with five replicates of 10 birds. The ducks were fed a corn and rice bran-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
0
7
2
1
Order By: Relevance
“…The duck eggs produced in this study are somewhat different from that reported by Ismoyowati et al [28]; the average egg production of Tegal ducks is 70.71%, with an average egg weight of 62.06 grams and egg yolk colour of 7.87. It is likely due to the length of observation, which Ismoyowati et al [28] did in 12 weeks, while in this study, the average production was for one year. The colour of the egg yolk produced in this study has a high score because the feed used is SPW, which can increase the colour of the yolk.…”
Section: Business Performancescontrasting
confidence: 96%
See 1 more Smart Citation
“…The duck eggs produced in this study are somewhat different from that reported by Ismoyowati et al [28]; the average egg production of Tegal ducks is 70.71%, with an average egg weight of 62.06 grams and egg yolk colour of 7.87. It is likely due to the length of observation, which Ismoyowati et al [28] did in 12 weeks, while in this study, the average production was for one year. The colour of the egg yolk produced in this study has a high score because the feed used is SPW, which can increase the colour of the yolk.…”
Section: Business Performancescontrasting
confidence: 96%
“…The red colour of egg yolks is caused by the SPW feed containing astaxanthin, which can provide a yellow tint to duck eggs [24]. The duck eggs produced in this study are somewhat different from that reported by Ismoyowati et al [28]; the average egg production of Tegal ducks is 70.71%, with an average egg weight of 62.06 grams and egg yolk colour of 7.87. It is likely due to the length of observation, which Ismoyowati et al [28] did in 12 weeks, while in this study, the average production was for one year.…”
Section: Business Performancescontrasting
confidence: 86%
“…[13] advocated using 0.33% temulawak as a feed additive in super-native chicken feed to produce optimal weight gain and final weight. According to [23], turmeric supplementation boosted egg production and egg quality of local ducks by 4% when compared to ginger. Some of the studies mentioned above demonstrate that administering herbal medicine has advantages.…”
Section: Fig 1 Percentage Of Mortality Loss and Rejected Ducksmentioning
confidence: 99%
“…In 2019 and 2020, duck egg production stood at 294 and 298 tonnes respectively, with an average duck egg production of 4% per year (Ditjenak, 2020). Various strains can be classified as local ducks, namely Tegal ducks (Anas javanicus), Alabio ducks (Anas platurynchos), Bali ducks (Anas, sp) and Mojosari ducks (Ismoyowati et al, 2022;FAO, 2016). However, the Mojosari duck is a candidate for development as a local duck and may potentially contribute animal protein to the people of Indonesia (Ismoyowati et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Various strains can be classified as local ducks, namely Tegal ducks (Anas javanicus), Alabio ducks (Anas platurynchos), Bali ducks (Anas, sp) and Mojosari ducks (Ismoyowati et al, 2022;FAO, 2016). However, the Mojosari duck is a candidate for development as a local duck and may potentially contribute animal protein to the people of Indonesia (Ismoyowati et al, 2022). Indonesia has developed either egg and meat from ducks (Sjofjan et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%